Chronic colitis upregulates microRNAs suppressing brain-derived neurotrophic factor in the adult heart. - Yanbo Tang (Public Library of Science (PLoS), 2021)
Ulcerative colitis and Crohn's disease are classified as chronic inflammatory bowel diseases (IBD) with known extraintestinal manifestations. The interplay between heart and gut in IBD has previously been noted, but the mechanisms remain elusive. Our objective was to identify microRNAs mediating molecular remodeling and resulting cardiac impairment in a rat model of colitis. To induce chronic colitis, dextran sodium sulfate (DSS) was given to adult rats for 5 days followed by 9 days with normal drinking water for 4 cycles over 8 weeks. Echocardiography was performed to evaluate heart function. DSS-induced colitis led to a significant decrease in ejection fraction, increased left ventricular mass and size, and elevated B-type natriuretic protein. MicroRNA profiling showed a total of 56 miRNAs significantly increased in the heart by colitis, 8 of which are predicted to target brain-derived neurotrophic factor (BDNF). RT-qPCR validated the increases of miR-1b, Let-7d, and miR-155. Transient transfection revealed that miR-155 significantly suppresses BDNF in H9c2 cells. Importantly, DSS colitis markedly decreased BDNF in both myocardium and serum. Levels of various proteins critical to cardiac homeostasis were also altered. Functional studies showed that BDNF increases cell viability and mitigates H2O2-induced oxidative damage in H9c2 cells, demonstrating its protective role in the adult heart. Mechanistically, cellular experiments identified IL-1β as the inflammatory mediator upregulating cardiac miR-155; this effect was confirmed in adult rats. Furthermore, IL-1β neutralizing antibody ameliorated the DSS-induced increase in miR-155 and concurrent decrease in BDNF in the adult heart, showing therapeutic potential. Our findings indicate that chronic colitis impairs heart function through an IL-1β→miR-155→BDNF signaling axis.